High-status individuals are held to higher ethical standards - Trautmann, Stefan T.; Wang, Xianghong; Wang, Yijie; Xu, Yilong (Scientific reports, 2023)
Although there is evidence for the generosity of high-status individuals, there seems to be a strong perception that the elites are selfish and contribute little to others’ welfare, and even less so than poorer people. We argue that this perception may derive from a gap between normative and empirical expectations regarding the behavior of the elites. Using large-scale survey experiments, we show that high-status individuals are held to higher ethical standards in both the US and China, and that there is a strong income gradient in normatively expected generosity. We also present evidence for a gap between people’s normative expectations of how the rich should behave, and their empirical expectations of how they actually do: empirical expectations are generally lower than both normative expectations and actual giving.